Predictors of Hydrops Fetalis Infants by Mode of Delivery (Journal of Obstetrics and Gynaecology of Eastern and Central Africa, 2024)
BACKGROUND: Hydrops fetalis is a fetal condition associated with higher perinatal and neonatal mortality and morbidity. The overall survival rate from the diagnosis is today estimated to be 27% despite advanced intrauterine and neonatal care. Factors that contribute to poor perinatal and neonatal outcomes have been identified; however, little is known about the existing specific predictor tool of perinatal outcome by mode of delivery. OBJECTIVE: the study aimed to determine whether cesarean section does improve the perinatal outcomes of hydrops fetalis infants.STUDY DESIGN: This was a retrospective cohort study that retrieved 102 medical records of pregnancies complicated by hydrops fetalis. For all those women, the transabdominal ultrasound was performed during pregnancy as part of the standard diagnostic modality of intrauterine hydrops fetalis. All pregnant women’s and their newborn’s medical records were retrieved and reviewed to collect information related to the outcomes as per the mode of delivery either by cesarean section or vaginal delivery. Based on the severity of fetal disease as described by obstetric ultrasound findings, pregnant women were divided into 4 groups: mild, moderate, moderately severe, and severe hydrops fetalis. The significance of the obtained data was set at two-tailed p